Peptidase Polymorphism in Natural Populations of the Cocoa Pest, Helopeltis theobromae Miller - Mohd Saahlan, Rusnah; Tan, Soon Guan; Muhamad Awang, Rita; Gan, Yik Yuen (1986)
Helopeltis theobromae caught off cocoa plants in Kuala Selangor and off Acalypha plants in Serdang, Selangor, Malaysia were investigated electrophoretically for nine biochemical markers: peptidase, a -glycerophosphate dehydrogenase, 6-phosphogluconate dehydrogenase, xanthine dehydrogenase, aldehyde oxidase, phosphoglucose isomerase, isocitrate dehydrogenase, glutamate transaminase and adenylate kinase. Only peptidase-2 polymorphism could be easily interpreted.